Analisis Perbandingan Syarat Jumlah Utang dalam Permohonan Kepailitan di Indonesia dengan Malaysia sebagai Bentuk Perlindungan Hukum bagi Debitor - Hendra Parulian; Handar Subhandi Bakhtiar; Atik Winanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Bankruptcy petitions in Indonesia are regulated under Article 2 paragraph (1) of Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU), which stipulates that a debtor may be declared bankrupt if they have at least two debts, one of which is due and collectible. However, this provision does not specify a minimum debt threshold as a requirement for bankruptcy, thereby creating a legal loophole that creditors may exploit by using bankruptcy as a mere debt collection tool. This raises concerns regarding the legal protection of debtors. This study aims to compare the bankruptcy laws of Indonesia and Malaysia, particularly with regard to the minimum debt amount requirement, and to evaluate whether the conditions for bankruptcy under the Indonesian Bankruptcy Law and PKPU provide legal certainty and adequate protection for debtors. The research employs a normative juridical method using statutory, conceptual, and comparative approaches. The findings indicate that the current provisions in Indonesia are no longer aligned with present-day needs and are prone to abuse. Unlike Malaysia, which stipulates a minimum debt amount, Indonesia has yet to regulate this matter explicitly. Therefore, a reformulation of Indonesia's bankruptcy law is necessary to ensure fairness, prevent misuse, and provide balanced legal protection for all parties, especially debtors.